Meet the Expert Jennifer Pahlka and Tim O'Reilly on Turbocharging Government's Response to the COVID-19 Crisis - Pahlka, Jennifer; O'Reilly, Tim (O'Reilly Media, Inc., 2020)
We've all seen the headlines: "States Overwhelmed by Previously Unimaginable Layoff Numbers"; "Here's What Is in the 'Families First' Coronavirus Aid Package"; "Local Governments Struggle to Obey Their Own Social Distancing Mandates." It's a perfect storm for government: unprecedented demand and urgent new programs to respond to the disaster at the same time as many government employees used to working face-to-face must suddenly work from home. Add to that a flood of stimulus money now, followed by a later drought as tax revenues are gutted by the economic shutdown, and two things are clear: people depend on government more than ever, and for government workers, getting better at providing digital services is no longer "nice to have" but "must have." In this Meet the Expert, Tim O'Reilly talks with Jennifer Pahlka, founder of Code for America, former deputy chief technology officer of the United States, and now cofounder of United States Digital Response, a new nonprofit connecting technology volunteers with governments that need their help. They discuss the new challenges governments face-and the resources that are available to meet them-and share case studies of how governments are fulfilling their mission in the present crisis. Recorded on April 21, 2020. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions
Online resource; Title from title screen (viewed April 28, 2020)
Keywords: COVID-19 (Disease) -- Government policy; Coronavirus infections -- Government policy; COVID-19; Politique gouvernementale; Infections à coronavirus; Politique gouvernementale; Electronic videos